MASS COMMUNICATION AND ENVIRONMENTAL EDUCATION: THE ROLE OF SOCIAL NETWORKS IN SOCIO-ENVIRONMENTAL MOBILIZATION - Fleury, João Felipe; Santos, Cinthya Amaral (Seven Editora, 2025)
This article discusses the interconnection between mass communication, social networks, and environmental education, emphasizing the importance of digital platforms in mobilizing and transforming social practices. The main objective is to examine how digital social networks intensify the dissemination of information related to the environment, encouraging collective mobilization and citizen participation in ecological issues. The study aims to analyze how digital communication can help overcome historical challenges faced by environmental education, such as curriculum fragmentation, lack of pedagogical resources, and the need for integration among different areas of knowledge. The research is grounded in the growing relevance of social networks as spaces for symbolic contestation, opinion formation, and social mobilization. In a context characterized by the rapid circulation of information, as well as the spread of false information and informational bubbles, it becomes essential to analyze methods that promote media and scientific literacy, enhancing individuals’ critical thinking and analytical skills. The central question addresses how digital social networks can function as effective instruments in environmental education, facilitating the development of ethical, critical, and transformative awareness in the face of contemporary socio-environmental challenges. The chosen methodological approach is qualitative, exploratory, and bibliographic, based on the analysis of scientific literature, official documents, and case studies of environmental campaigns carried out on social networks, including both national and international examples. DOI: https://doi.org/10.56238/sevened2025.038-066